2012
DOI: 10.1155/2012/792649
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Contraceptive Needs of Key Populations Affected by HIV in Asia: An Unfinished Agenda

Abstract: Like all women, women living with and at risk of acquiring HIV have the right to determine the number and timing of their pregnancies and to safely achieve their reproductive intentions. Yet, many women in Asia affected by HIV lack access to family planning services and experience disproportionately high rates of unintended pregnancy and abortion. Programs that have succeeded in promoting condom use and providing HIV prevention and treatment services in this region have largely missed the opportunity to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…8 While promotion of methods other than condoms is often a concern in HIV programs, the evidence suggests that individuals at high risk for HIV do not substitute other methods for condoms. 2,8,25 Our data clearly show that female sex workers recognize the need for condoms for disease prevention, regardless of whether they are using another contraceptive method. Female sex workers need a wide range of reproductive health services, and participants in our study relied primarily on the private sector (including drug shops) and NGOs when they sought care.…”
Section: Health Care Experiences and Preferencesmentioning
confidence: 70%
See 3 more Smart Citations
“…8 While promotion of methods other than condoms is often a concern in HIV programs, the evidence suggests that individuals at high risk for HIV do not substitute other methods for condoms. 2,8,25 Our data clearly show that female sex workers recognize the need for condoms for disease prevention, regardless of whether they are using another contraceptive method. Female sex workers need a wide range of reproductive health services, and participants in our study relied primarily on the private sector (including drug shops) and NGOs when they sought care.…”
Section: Health Care Experiences and Preferencesmentioning
confidence: 70%
“…Among women who had visited a provider, the service most often used was STI testing and treatment (77-81% of women in the two groups), followed by maternal and child health services (32-53%) and treatment for injuries related to violence it may be tempting to try to meet all of the sexual and reproductive health service needs of female sex workers at a single site, we must bear in mind that integration can present logistical and other challenges, such as ensuring adequate staffing, training and space and maintaining quality of services. 2,5 One pressing need that stands out is that for services and interventions that address gender-based violence. Levels of such violence are high in Bangladeshi society in general, and are particularly high among female sex workers.…”
Section: Health Care Experiences and Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…[140][141][142] High rates of abortion have been reported among women who use drugs, some of whom are also sex workers, however, reduction in abortion-related risks and integration of family planning and post-abortion care in this population has not adequately been documented. [143][144][145] Fertility-related assessments prior to pregnancy in this population are limited, although studies focused on women living with HIV in Canada, including women who use drugs, suggested that drug use did not affect fertility intentions. 146 Evidence-based and human rightsaffirming interventions are needed at this time when certain programming efforts incentivize contraceptive use or sterilization among women who use drugs.…”
Section: Women Who Use Drugsmentioning
confidence: 97%